Efficacy and Safety of Dual Antiplatelet Therapy Versus Direct Oral Anticoagulant Following Left Atrial Appendage Closure: : A Systematic Review and Meta-Analysis - Patel, Neha (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.